Prevalência de sibilância em lactentes nas unidades básicas de saúdedo município de Belo Horizonte-MG - Silvia de Souza Campos Fernandes (2009)
The prevalence of recurrent wheezing in early childhood greatly varies inworld-wide population. It may be the clinical expression of many lung diseases or not, being asthma one of them, so it is a clinical syndrome. The great variation in prevalence is related to different definitions, study designs and considered age groups. Its evaluation poses a big challenge and it aims at the preventable and educational measures that must be applied. This dissertation was made as two articles. The first one consisted of a systematic review of literature from searches on the databases MEDLINE and LILACS in the period of 1999- 2008, with 163 articles identified and 26 that were selected as expressives. Theprevalence of wheezing in children below 5 years varied from 2,8% to 80,3%. These findings were related to environmental and socioeconomic conditions; at countries in development, environmental pollution and respiratory infections at the first year of life were causative factors contrarily to developed countries where the history of allergy andthe exposition to furred animals were more frequent. The second article is a cross-sectional survey for evaluating the prevalence of wheezing among 1261 infants from 12 to15 months of age attending at health units of Belo Horizonte, Brazil in the year of 2005. Their parents or legal guardians answered the written questionnaire EISL (Estudio Internacional de Sibilancias en Lactentes). The prevalence of wheezing was 52% and of recurrent wheezing was 28,4% and in this population the search for emergencies was 63,2% and for hospitalizations was 70,1%. So it was confirmed the elevated frequency of recurrent wheezing in Belo Horizonte and the contribution of this entity for emergency departmentadmissions and for hospitalizations, demanding for preventive and educative actions by Public Health.